Achieving stable nitritation for mainstream anammox by combining nitrite exposure inhibition with high DO reactivation. (April 2022) - Cui, Huihui; Zhang, Liang; Peng, Yongzhen; Zhang, Qiong; Li, Xiyao
Abstract: This study achieved stable nitritation by eliminating both Nitrobacter and Nitrospira through combing nitrite exposure inhibition with high dissolved oxygen (DO) reactivation. After treated by nitrite exposure (5–30 mg·L −1 ), nitrite-oxidizing bacteria (NOB) of two nitrifying reactors (RL and RH ) was suppressed seriously than ammonium-oxidizing bacteria (AOB) with faster activity decay rate (0.035 ± 0.003 d −1 ) and larger population reduction as well as slower functional gene transcription, wherein Nitrobacter was inhibited more significantly than Nitrospira . During reactivation period, the RH (high DO: 2.5–3.0 mg·L −1 ) achieved nitritation with high NAR of 97.9%, which was twice faster than RL (low DO: 0.1–0.6 mg·L −1 ). Though temperature declined to 16.6 °C, RH remained constant nitritation with ideal effluent NO2 − -N:NH4 + -N of 1:1 for anammox. Further analysis indicated that high DO reactivation accelerated AOB overcome NOB by promoting AOB growth but severely inhibited Nitrospira . The findings provided novel insights into suppressing NOB in targeted ways which facilitated mainstream deammonifcation. Graphical abstract: Unlabelled Image Highlights: Stable nitritation rapidly achieved by combining nitrite exposure and high DO reactivation Nitrite exposure suppressed Nitrobacter to a more severe extent than Nitrospira . Reactor in high DO level achieved nitritation in 18 d with ideal NO2 − -N:NH4 + -N of 1:1. High DO reactivation promoted rapid growth of AOB but severely inhibited Nitrospira . Nitritation stabled with NAR above 97% even temperature reduced from 26.6 °C to 16.6 °C.